Impacts of pulsed electric field and heat treatment on quality and sensory properties and microbial inactivation of pomegranate juice - Evrendilek, Gulsun A (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2017)
Synergistic effects of pulsed electric field+mild heat on quality properties of pomegranate juice were modeled using the best-fit multiple (non-) linear regression models with inactivation kinetics parameters of Escherichia coli O157:H7 and Staphylococcus aureus. No significant difference was detected between the control and the treated samples in terms of pH; °Brix; total antioxidant capacity; total monomeric anthocyanin content; total ascorbic acid concentration; and the sensory properties of flavor, taste, aftertaste, and overall acceptance ( p > 0.05). An exposure of 65.3 J and 40 ℃ caused an increase on conductivity; titratable acidity; L*, a*, and b* values; and a decrease of browning index, total phenolic content, total antioxidant capacity, total monomeric anthocyanin content, total ascorbic acid concentration, and in the sensory properties of color and sourness in pomegranate juice. The goodness-of-fit for the best-fit multiple (non-) linear regression models in descending order belonged to E. coli O157:H7 (92.98%), S. aureus (84.06%), color a* (83.9%), titratable acidity (81.3%), color L* (78.5%), color b* (78.3%), conductivity (74.8%), total phenolic content (74.1%), and total ascorbic acid concentration (64.74%), respectively. De and ze values for E. coli O157:H7 and S. aureus ranged from 105.64 to 1093.25 and from 79.18 to 1057.73 µs with 27.39 and 30.80 J, consequently